The Relationship Between Mother's Attitude and Behavior to The Nutritional Status of Preschool Children in Kalanganyar District, Lebak, Banten and Its Overview from An Islamic - Fakhiroh, Lulu; Indrawati, Isna; Istiwara, Endy Muhammad (Junior Medical Journal, 2023)
Background: The nutritional status of children under five is one measure of the success of health development, therefore it is necessary to pay attention to the nutrition of children under five. Factors that affect nutritional status can be divided into direct and indirect factors. Direct factors are determined by food intake and infectious diseases, while indirect factors include the availability of food in the family, parenting patterns, health services and environmental conditions. The purpose of this study was to describe the nutritional status of preschool children in Kalanganyar Lebak District, Banten. To find out the picture of parenting style on the nutritional status of preschool children in the District of Kalanganyar Lebak, Banten. To determine the relationship between maternal parenting behavior and the nutritional status of preschool children in Kalanganyar Lebak District, Banten. The method in this study used a quantitative type with correlation analytic, namely to see the relationship between attitudes and behavior of mother's parenting pattern towards the nutritional status of preschool children in Kalanganyar District, Lebak, Banten. Result: The results of this study from the bivariate test showed a p value of 0.0024 <0.05 which means that there is a relationship between mother's parenting behavior and children's nutritional status. The results of the bivariate analysis test showed a p value of 0.034 <0.05 which means that there is a relationship between mother's parenting behavior and children's nutritional status. Conclusion: The conclusion from this study is that there is a relationship between maternal parenting behavior and the nutritional status of preschool children in Kalanganyar District, Lebak Banten. There is a relationship between mother's parenting behavior and nutritional status of preschool children in the Kalanganyar sub-district, Lebak, Banten.